Improving the south America wildfires smoke estimates: Integration of polar-orbiting and geostationary satellite fire products in the Brazilian biomass burning emission model (3BEM). (15th March 2022) - Pereira, Gabriel; Longo, Karla M.; Freitas, Saulo R.; Mataveli, Guilherme; Oliveira, Valter J.; Santos, Paula R.; Rodrigues, Luiz F.; Cardozo, Francielle S.
Abstract: Large land extensions are subjected to environmental degradation and land-use changes by fires annually. In tropical regions, such as South America, the global demand for commodities leads to the conversion of natural vegetation into agricultural land-uses. With the new orbital fire products that have improved in spatial and temporal resolution, it is now possible to better understand fire properties at large scales, such as fire radiative power (FRP), fire spread, heat flux, and fire life cycle. This study aims to integrate polar-orbit and geostationary satellites' fire-related products to estimate biomass burning (BB) emissions on a continental-scale to better monitor smoke plumes in near-real-time (NRT) while using the Brazilian developments on the Regional Atmospheric Modeling System (BRAMS). The total aerosol optical depth at 550 nm channel from the model during the South American 2020 fire season (September–November) showed a good agreement with Modern-Era Retrospective analysis for Research and Applications (MERRA-2) and Copernicus Atmosphere Monitoring Service (CAMS) Global Near-Real-Time reanalyzes (R = 0.97, p < 0.05, student t-test). Moreover, the new improvements made in the Brazilian Biomass Burning Emission Model with fire radiative power (3BEM-FRP) better represent smoke emissions of large fire events, such as the Pantanal 2020 fires. Highlights: Merging polar-orbiting and geostationary sensors improve estimates of fire emissions. FRP better represents smoke emissions of large fire events than burned area. Simulated smoke plume in South America showed a good agreement with MERRA-2 and CAMS. Misdetection of small fires contributes to uncertainties and inaccuracies of emissions. Atmosphere-related estimates derived from FRP remain a challenging task.